A multitransmit external body array combined with a 1H and 31P endorectal coil to enable a multiparametric and multimetabolic MRI examination of the prostate at 7T. Issue 9 (1st August 2019) - Philips, Bart W. J.; van Uden, Mark J.; Rietsch, Stefan H. G.; Orzada, Stephan; Scheenen, Tom W. J.
Abstract : Purpose: In vivo 1 H and 31 P magnetic resonance spectroscopic imaging (MRSI) provide complementary information on the biology of prostate cancer. In this work we demonstrate the feasibility of performing multiparametric imaging (mpMRI) and 1 H and 31 P spectroscopic imaging of the prostate using a 31 P and 1 H endorectal radiofrequency coil (ERC) in combination with a multitransmit body array at 7 Tesla (T). Methods: An ERC with a 31 P transceiver loop coil and 1 H receive (Rx) asymmetric microstrip ( 31 P/ 1 H ERC) was designed, constructed and tested in combination with an external 8‐channel 1 H transceiver body array coil (8CH). Electromagnetic field simulations and measurements and in vivo temperature measurements of the ERC were performed for safety validation. In addition, the signal‐to‐noise (SNR) benefit of the 1 H microstrip with respect to the 8CH was evaluated. Finally, the feasibility of the setup was tested in one volunteer and three patients with prostate cancer by performing T2 ‐weighted and diffusion‐weighted imaging in combination with 1 H and 31 P spectroscopic imaging. Results: Electromagnetic field simulations of the 31 P loop coil showed no differences in the E‐ and B‐fields of the 31 P/ 1 H ERC compared with a previously safety validated ERC without 1 H microstrip. The hotspot of the specific absorption rate (SAR) at the feed point of the 31 P/ 1 H ERC loop coil was 9.42 W/kg when transmitting on 31 P at 1 W. Additional in vivo measurements showed a maximum temperature increase at the SAR hotspot of 0.7°C over 6 min on 31 P at 1.9 W transmit (Tx) power, indicating safe maximum power levels. When transmitting with the external 1 H body array at 40W for 2:30 min, the temperature increase around the ERC was < 0.3°C. Up to 3.5 cm into the prostate the 1 H microstrip of the ERC provided higher SNR than the 8CH. The total coil combination allowed acquisition of an mpMRI protocol and the assessment of 31 P and 1 H metabolites of the prostate in all test subjects. Conclusion: We developed a setup with a 31 P transceiver and 1 H Rx endorectal coil in combination with an 8‐channel transceiver external body array coil and demonstrated its safety and feasibility for obtaining multiparametric imaging and 1 H and 31 P MRSI at 7T in patients with prostate cancer within one MR examination.